Experimental substantiation of application of adrenoblocators for the treatment of patients with generalized parodont - Kononova, O. (Actual Dentistry, 2018)
Abstract. In the development of periodontal diseases, the presence of psychological stress in patients is important. This should be taken into account in case of complex treatment of patients with periodontal diseases. To effectively treat periodontal diseases in these patients, it is necessary to experimentally substantiate the effectiveness of the proposed complex of adrenoblockers. Objective. Experimentally substantiate the effectiveness of the proposed complex of adrenoblockers for the treatment of periodontal diseases. Methods. To substantiate the effectiveness of the proposed complex of adrenoblockers for the treatment of periodontal diseases, an experimental study was conducted on animals. Adrenaline stress was made in rats by oral application of gel with adrenalin in dose 0,36 mg/kg during 10 days. Lincomycin was introduced with drinking water in dose 60 mg/kg. T he gel of adrenoblocators (zocson + nicergolin and sibason) was introduced by application in dose 0.6 mg/kg. Conents of glucose, triglycerides, total cholesterine and malonic dialdehide (MDA), the activities of urease, lysozyme, elastase and catalase were determined into serum. Histological researches were made with used hematoxilyn and eosin. Results. The conducted experimental studies have shown that the development of adrenalin stress causes in animals to increase the level of elastase, malonic dialdehyde. At the same time, the activity of catalase, antioxidant-prooxidative index decreases. The adrenoblocator gel reduced activity urease and content MDA, but raised activity catalase and antioxidant-prooxidative index. The results of histologic investigations showed periodontoprotective action of adrenoblockators. Conclusions. Oral application of gel with adrenoblocators made antidysbiotic action more then quertulyne, but yielded in antiinflammation and antioxidative actions to quertulyne after common introduce adrenaline and lincomycin. Thus, application of a gel with adrenoblockers produces an anti-inflammatory effect, but more definitely normalizes the processes of peroxidation of lipids. Key words: periodontal diseases, adrenaline stress, adrenoblocator, inflammation, antioxidant.